Breech Presentation in Twins as a Risk Factor for Developmental Dysplasia of the Hip. Issue 1 (January 2022) - Oh, Eun Ji; Min, Jae Jung; Kwon, Soon-Sun; Kim, Seong Been; Choi, Chang Won; Jung, Young Hwa; Oh, Kyung Joon; Park, Jee Yoon; Park, Moon Seok
Abstract : Introduction: Identifying risk factors associated with developmental dysplasia of the hip (DDH) is essential for early diagnosis and treatment. Breech presentation is a major DDH risk factor, possibly because of crowding of the fetus within the uterus. In multifetal pregnancy, fetuses are generally smaller than singletons, which may obscure the effect of breech presentation on fetal hips. Only a few studies have investigated the occurrence of DDH in multifetal pregnancies. In this study, we aimed to evaluate whether the breech presentation is a major risk factor of DDH in twin pregnancies. Methods: This retrospective study included 491 consecutive live births (after 23+0 weeks gestation) delivered through cesarean section with at least 1 baby with noncephalic presentation in single or twin pregnancies from April 2013 to October 2018. We analyzed the incidence of DDH and its associated factors, including sex, breech, and multifetal pregnancy, with a generalized linear mixed model. Results: The incidence of DDH was 12.5% in singleton with breech presentation, 9.8% in twin-breech presentation, and 0.7% in twin-cephalic presentation. Multivariate analysis showed that singleton-breech presentation ( P =0.003), twin-breech presentation ( P =0.003), and female sex ( P =0.008) were independent risk factors for DDH. Conclusion: Breech presentation is an independent risk factor for DDH in twin pregnancies, although twin pregnancy itself is not an independent risk factor for DDH.